2015
DOI: 10.1039/c5dt01222h
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled BiVO4/Bi2WO6 microspheres: synthesis, photoinduced charge transfer properties and photocatalytic activities

Abstract: Three-dimensional (3D) BiVO4/Bi2WO6 composite microspheres with enhanced visible-light (λ > 420 nm) photodegradation activity of methylene blue (MB) were synthesized by a simple, one-pot, template-free solvothermal method. A mixture of ethylene glycol (EG) and H2O (volume ratio of EG-H2O was 1 : 1) was used as the solvent. To investigate the relationship between structure and photocatalytic performance, the as-synthesized samples were characterized by XRD, FESEM, HRTEM, UV-vis DRS, SPS and TPV. Structural char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…On the other hand, there was a competition between nucleation and crystallization in Bi 2 WO 6 and BiVO 4 in the reaction, slowing down the formation of flower-like Bi 2 WO 6 microspheres compared to previous reports. 56 Then, BiVO 4 nanoparticles gradually crystallized and precipitated during the reaction process and formed 2D nanoplates in an additional crystallization process. Subsequently, Bi 2 WO 6 and BiVO 4 grew together.…”
Section: Growth Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there was a competition between nucleation and crystallization in Bi 2 WO 6 and BiVO 4 in the reaction, slowing down the formation of flower-like Bi 2 WO 6 microspheres compared to previous reports. 56 Then, BiVO 4 nanoparticles gradually crystallized and precipitated during the reaction process and formed 2D nanoplates in an additional crystallization process. Subsequently, Bi 2 WO 6 and BiVO 4 grew together.…”
Section: Growth Mechanismmentioning
confidence: 99%
“…Zhang et al 53 firstly reported the preparation of a Bi 2 WO 6 /BiVO 4 heterojunction with higher photocatalytic activity than the individual components under visible light irradiation; 81% of phenol was degraded in 6 h, indicating that the combination of Bi 2 WO 6 and BiVO 4 could obviously enhance the photocatalytic activity of pure Bi 2 WO 6 . Subsequently, Chaiwichian et al, 54 Xue et al 55 and Fan et al 56 prepared Bi 2 WO 6 /BiVO 4 heterojunction photocatalysts via different preparation methods, and these displayed enhanced visible light photocatalytic activity in the degradation of dyes. In addition, in our previous report, 57 a calcined Bi 2 WO 6 /BiVO 4 heterojunction photocatalyst with a multilayer plate-like structure was synthesized via a hydrothermal-calcination method and exhibited enhanced photocatalytic activity in the degradation of RhB; the degradation efficiency reached 100% within 30 min.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to exploit novel photocatalysts with high visible-light photocatalytic performances and high stability. Up to now, bismuth-based photocatalysts have received extensive attention for their potential applications in environmental decontamination and hydrogen energy production by utilization of solar light energy, such as, Bi 2 MoO 6 , 6 BiVO 4 , 7 BiWO 4 , 8 BiOR (R = Cl, Br, I) [9][10][11] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Two-step process (hydrothermal and calcination) was applied to obtain uniform morphology and better crystallinity of the BVO/BWO composite leading to superior visible-light absorption and higher photodegradation activity for RhB [22]. Moreover, forming of BVO/BWO heterojunction facilitated electron-hole separation and charge transfer, which promoted photocatalytic activity [23,24].…”
Section: Introductionmentioning
confidence: 99%